Generic drug product development : solid oral dosage forms - Shargel, Leon, 1941-; Kanfer, Isadore (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2014)
'This book collects in-depth discussions from more than 30 noted specialists on topics such as quality control, experimental formulations, pharmaceutical ingredients, conventional and modified-release products, and bioequivalence. It considers key elements in the formulation of generic drug products including the availability of raw materials and chemical purity. It contains new chapters on experimental formulation development, and the relationship between the FDA and the United States Pharmacopeia'--Provided by publisher.
Active pharmaceutical ingredient / Edward M. Cohen, Steven Sutherland -- Analytical methods development and methods validation for solid oral dosage forms / Quanyin Gao, Dilip R. Sanvordeker -- Experimental formulation development / Isadore Kanfer ... [et al.] -- Scale-up, technology transfer, and process performance qualification / Salah U. Ahmed ... [et al.] -- Drug stability / Pranab K. Bhattacharyya -- Quality control and quality assurance / Loren Gelber -- Drug product performance, in vitro / Pradeep M. Sathe, John Duan, and Lawrence X. Yu -- ANDA regulatory approval process / Timothy W. Ames, Aaron Sigler -- Bioequivalence and drug product assessment, in vivo / Barbara M. Davit, Dale P, Conner -- Statistical considerations for establishing bioequivalence / Charles Bon, Sanford Bolton -- Outsourcing bioavailability and bioequivalence studies to contract research organizations / Patrick K. Noonan -- Post-approval changes and post-marketing surveillance / Lorien Armour, Leon Shargel -- United States Pharmacopeia-National Formulary : its history, organization, and role in harmonization / William Brown, Margareth R.C. Marques -- Legal and legislative hurdles to generic drug development, approval and marketing / Arthur T. Tsien.
Includes bibliographical references and index.
Keywords: Drugs, Generic -- standards; Chemistry, Pharmaceutical -- standards; Drug Approval; Tablets; Generic drugs; Solid dosage forms